HEDONIC QUALITY OF SEMPRONG CAKE FROM VARIOUS LEVELS OF CATFISH FLOUR ADDITION - Halyda Aulia Wildah; Junianto Junianto; Ine Maulina; Iis Rostini (Universitas Mataram, 2024)
Diversification of processed fisheries is very important to attract the interest of the Indonesian people who still have low consumption of fish. The addition of catfish meat flour to semprong cake is expected to increase the nutritional value and attract consumer attention. The aim of this research was to determine the level of addition of catfish meat flour to semprong cakes as the product most preferred by panelists based on hedonic quality which includes aspects of appearance, aroma, texture and taste. This research used an experimental method with four treatments adding catfish meat flour at 0%, 12.5%, 15% and 17.5%. Data analysis using tests friedman, multiple comparison and Bayes. The results of the research showed that the level of addition of catfish meat flour of 15% was the most preferred addition in terms of appearance with a mean value of 8.7 (like), aroma 7.7 (like), and taste 7 (like), while the addition was 12%. was the most liked addition in terms of texture with a mean value of 7.2 (like). It was concluded that the addition of 15% was the most preferred treatment in terms of appearance, aroma and taste and the addition of 12.5% was the most preferred treatment in terms of texture.